2019
DOI: 10.1182/blood.2019000200
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α–driven inflammation and mitochondrial dysfunction define the platelet hyperreactivity of aging

Abstract: Aging and chronic inflammation are independent risk factors for the development of atherothrombosis and cardiovascular disease. We hypothesized that aging-associated inflammation promotes the development of platelet hyperreactivity and increases thrombotic risk during aging. Functional platelet studies in aged-frail adults and old mice demonstrated that their platelets are hyperreactive and form larger thrombi. We identified tumor necrosis factor α (TNF-α) as the key aging-associated proinflammatory cytokine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
173
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(214 citation statements)
references
References 61 publications
(61 reference statements)
20
173
3
1
Order By: Relevance
“…In this context, clinical trials are currently underway to determine the impact of anticoagulants (e.g., heparin) or pro-fibrinolytic drugs (e.g., tissue plasminogen activator) in ameliorating severe COVID-19 infection with thromboembolic complications (21). Interestingly, platelets from older subjects are hypercoagulable in the presence of pro-inflammatory stimuli (22), which may help explain the increased mortality rates in older COVID-19 patients. Of note, small molecule metabolites are relevant in treating coagulopathies (e.g., tranexamic acid to treat hyperfibrinolysis in actively bleeding patients) (23).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, clinical trials are currently underway to determine the impact of anticoagulants (e.g., heparin) or pro-fibrinolytic drugs (e.g., tissue plasminogen activator) in ameliorating severe COVID-19 infection with thromboembolic complications (21). Interestingly, platelets from older subjects are hypercoagulable in the presence of pro-inflammatory stimuli (22), which may help explain the increased mortality rates in older COVID-19 patients. Of note, small molecule metabolites are relevant in treating coagulopathies (e.g., tranexamic acid to treat hyperfibrinolysis in actively bleeding patients) (23).…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] A recent study also reported the platelet hyperreactivity of aging through TNF‐α‐driven inflammation and mitochondrial dysfunction in mice. [ 22 ] These results suggest an interaction of platelet and TNF‐α in D‐GalN sensitized ALF mice. However, how these processes affect rapid development of ALF which requires further extensive studies.…”
Section: Figurementioning
confidence: 85%
“…Flow cytometry data were analyzed using Kaluza flow analysis software (Beckman Coulter) and Flowjo (Flowjo, LLC). Gating strategy as previously described (Davizon‐Castillo et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%